Implementation Distortion of Indonesian Health Card (KIS)-Contribution Assistance Recipients (PBI): Studies in Jakarta, Bogor, and Depok - Muthmainnah, Yulianti (Yayasan Jurnal Perempuan, 2017)
This paper not only narrated the National Social Security System in Healthcare, but also findings of fact of the direct field practice of the registration of Indonesian Health Card (KIS)-Contribution Assistance Recipients (PBI) for poor women, minorities, and other vulnerable groups in the poor area of Jakarta, Bogor, and Depok. This research undertaken by students of semester 5th Department of Primary School Teacher Education UHAMKA during October-December 2016 to fulfill the task of â€œibadah sosialâ€ (social worship) onsubjects Kemuhammadiyahan.